113 Identification and correction of bowel injuries as a result of perforation with a uterine manipulator, using the robotic platform. (18th September 2019) - Pedra Nobre, S; Filippova, OT; Leitao, M
Abstract : Objectives: To demonstrate use of the robotic platform to identify and repair intraoperative bowel injuries secondary to perforation with a uterine manipulator. Methods: We present video footage and still photographs of bowel injuries after perforation with a uterine manipulator, in a patient with grade 2 endometrial cancer. Results: We demonstrate the identification of both large and small bowel defects after perforation with a uterine manipulator, and their correction using the robotic platform. Emphasis is placed on key components of the procedure, including correctly identifying anatomy, avoiding immediate removal of the manipulator so as to clearly identify the extent of the defect, and meticulous adhesiolysis and suturing technique. A through-and-through defect in the sigmoid colon is identified, and both sides are repaired in two layers using 3–0 PDS suture in a running fashion. The first layer is run, incorporating full thickness bites to reapproximate the bowel mucosa. A second, imbricating layer is placed with interrupted suture to reinforce this closure. Another defect is identified in the small bowel, and repaired similarly; however, both the first and second layers are placed in an interrupted fashion. Both defects are closed to avoid narrowing the lumen of the bowel. The bowel is then run in its entirety to identify any other defects. Conclusions: We demonstrate that with prompt identification, gradual removal of the manipulator, and careful dissection, correction of bowel injury after perforation with a uterine manipulator can be achieved using the robotic platform, without obligatory conversion to laparotomy.